Aloe Gel Enhances Angiogenesis in Healing of Diabetic Wound - Djanggan Sargowo; Adeodatus Yuda Handaya; Mohammad Aris Widodo; Diana Lyrawati; Askandar Tjokroprawiro (The Indonesian Biomedical Journal, 2011)
BACKGROUND: Diabetic micro and macroangiophathy lead to the incident of diabetic foot ulcers characterized by an increased number of circulating endothelial cells (CECs) and decreased function of endothelial progenitor cells (EPCs). This fact is correlated with ischemia and diabetic wound healing failure. Aloe vera gel is known to be able to stimulate vascular endothelial growth factor (VEGF) expression and activity by enhancing nitric oxide (NO) production as a result of nitric oxide synthase (NOS) enzyme activity. Aloe vera is a potential target to enhancing angiogenesis in wound healing.OBJECTIVE: The objective of this study was to explore the major role of Aloe vera gel in wound healing of diabetic ulcers by increasing the level of EPCs, VEGF, and endothelial nitric oxide synthase (eNOS), as well as by reducing the level of CECs involved in angiogenesis process of diabetic ulcers healing.METHODS: The experimental groups was divided into five subgroups consisting of non diabetic wistar rats, diabetic rats without oral administration of aloe gel, and treatment subgroup (diabetic rats) with 30, 60 and 120 mg/day of aloe gel doses for 14 days. All subgroups were wounded and daily observation was done on the wounds areas. Measurement of the number of EPCs (CD34), and CECs (CD45 and CD146) was done by flowcytometry, followed by measurement of VEGF and eNOS expression on dermal tissue by immunohistochemical method on day 0 and day 14 after treatment. The quantitative data were analyzed by One-Way ANOVA and Linear Regression, with a cofidence interval 5% and significance level (p<0.05) using SPSS 16 software to compare the difference and correlation between wound diameters, number of EPCs and CECs as well as the levels of VEGF and eNOS.RESULTS: The results of this study showed that aloe gel oral treatment in diabetic wistar rats was able to accelerate the wound healing process. It was shown by significant reduction of wound diameter (0.27±0.02); the increased number of CECs (0.42±0.57), respectively (p<0.05). On the other hand, the wound diameter and eNOS indicators showed significant differences at the dose of 60 mg, while the number of EPCs and CECs and the level of VEGF showed significantly different results at a dose of 120 mg. Aloe gel oral therapy showed a positive indication of wound healing acceleration at the optimum dose range 60-120 mg a day.CONCLUSIONS: Aloe gel is potential to be a herbal therapy candidate for diabetic wound healing through enhancing EPCs homing, decreasing the CECs number, and stimulating the increase of VEGF and eNOS levels,hence proving to be a dominant factor in the angiogenesis process.KEYWORDS: aloe gel, diabetes, wound healing, angiogenesis